Digital documentary of Uraklawoi young childrens play in a changing society on the West Coast of Thailand: The medium for implications of the ethnological study - YAOWALUK SUWANNAKHAE (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: This ethnological study explored the adult’s perception about how the UrakLawoi young children’s Play is changing over time and the correlation of plays and the child’s developmental domains.Method: Participants in the study were recruited from accurately conveying oral traditions, written evidence, and relevant documents. Also selected were local experts who were able to provide supporting information through extensive interviewing accurately. Data were collected through document studies, and fieldwork carried out in Ban Hau Laem, in the Sanga-U Village, in Toe Ba Liew Village at KohLanTaYai, Krabi Province, BanLeamTukkae, and KohSiReh in Phuket Province.Findings: Findings showed that UrakLawoi young children’s play enhanced the development of their social skills in particular areas, such as making friends and positive interaction in group settings, communication and language practices, fine motor skills development, as well as the unearthing of their ancestry, history, rituals, and related stories. Also, a Digital Documentary titled UrakLawoi Young Children’s Play was produced in DVD format from the findings. Also, the video clips were made accessible on YouTube and composed of 5 parts; the UrakLawoi origin, Pulao Satuk (Koh Lanta), Play, the UrakLawoi Young Children’s Play as a life skill, and the Confidant.Implications/Novel Contribution: The findings of this study are expected to help families, education systems, and societies explore how to augment better the cognitive, emotional, physical, and language growth capabilities of Chaolay children while also maintaining modes of Play that contribute to UrakLawois culture and history.